Is there a gender gap in equity-based crowdfunding? - Jörg Prokop; Dandan Wang (Small Business Economics, 2021)
Compared to their male peers, female entrepreneurs tend to face greater obstacles in raising venture funding from business angels, venture capitalists, and financial institutions. In this paper, we investigate whether this gender gap also exists in equity crowdfunding. Based on data from the German equity crowdfunding market, we find that ventures with and without female managing directors are equally successful in raising capital when launching their first equity crowdfunding campaign. In contrast, the former are significantly less successful than their peers in seasoned equity crowdfunding campaigns, and this disparity cannot be fully explained by differences in other venture-related or entrepreneur-related characteristics. However, we also find that the gender gap in seasoned offerings narrows if female entrepreneurs set more ambitious funding thresholds. Overall, our results indicate that pitching their equity crowdfunding campaigns in a more promotion-oriented way is a sensible strategy for female entrepreneurs to improve funding success.
Keywords: G32; J16; O16; 330; Crowdinvesting; Entrepreneur; Equity-based crowdfunding; Female entrepreneur; Gender gap; Venture financing